2021
DOI: 10.1111/jam.14988
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid‐resistant MRSA‐CC398 carrying the cfr gene, and MRSA‐CC9 isolates from pigs with signs of infection in Spain

Abstract: Aims: To perform the molecular characterization of 23 Staphylococcus aureus isolates from pigs with signs of infections recovered in Spanish farms during 2018-2019. Methods and Results: The antimicrobial resistance pattern and virulence profile were determined. The molecular typing was performed by different molecular techniques. The transferability of the cfr gene was assessed by conjugation and its genetic environment was determined by PCR mapping. In all, 21 isolates were methicillin-resistant S. aureus (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
(130 reference statements)
1
12
0
Order By: Relevance
“…Previous studies reported the presence of MRSA from ST398 with the same spa -type observed in pigs, in humans in close contact with pig farms [ 3 , 11 , 20 ]. The emergence of cfr -mediated linezolid resistance in MRSA from animal origin has also been reported in horses in Germany [ 26 ], pigs in Belgium [ 27 ], Korea [ 28 ], China [ 29 ], and Spain [ 30 ], and poultry in China [ 29 ]. Moreover, cfr -positive MRSA strains have been reported sporadically in humans in several European countries, including Italy [ 31 ], Portugal [ 14 ], Spain [ 32 ], as well in hospital outbreaks in Spain [ 33 ] and China [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the presence of MRSA from ST398 with the same spa -type observed in pigs, in humans in close contact with pig farms [ 3 , 11 , 20 ]. The emergence of cfr -mediated linezolid resistance in MRSA from animal origin has also been reported in horses in Germany [ 26 ], pigs in Belgium [ 27 ], Korea [ 28 ], China [ 29 ], and Spain [ 30 ], and poultry in China [ 29 ]. Moreover, cfr -positive MRSA strains have been reported sporadically in humans in several European countries, including Italy [ 31 ], Portugal [ 14 ], Spain [ 32 ], as well in hospital outbreaks in Spain [ 33 ] and China [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Filter mating experiments were performed to investigate whether the cfr carrying plasmid is conjugative. Using a clinical isolate S. aureus 719 (ST5, cfr negative) and ATCC29213-rifR as recipients and S. capitis LZD1 and LZD8 as donors with selection on nutrient agar plates containing 4 mg L −1 linezolid and 12.5 mg L −1 tetracycline or plates containing 4 mg L −1 linezolid and 50 mg L −1 rifampin according to the reference with adjustment in antibiotic concentrations 49 , 50 . The transconjugants were identified using MALDI-TOF and PCR of cfr gene with primers ( cfr -fw: TGAAGTATAAAGCAGGTTGGGAGTCA; cfr -rv: ACCATATAATTGACCACAAGCAGC) 51 .…”
Section: Methodsmentioning
confidence: 99%
“…These include ESBLs or fluoroquinolone resistance in Enterobacterales and/or Campylobacter in poultry and dairy production or LA‐MRSA in pigs. Some studies have also searched databases, or conducted limited field studies for newly emerging resistances that have been initially reported in animal production outside the EU, such as carbapenem and mcr ‐related transferable colistin ARGs (Bennani et al., 2020; Irrgang et al., 2020; Caffrey et al., 2021; Jochum et al., 2021; Ruiz‐Ripa et al., 2021). Less well‐researched or readily culturable organisms, such as C. difficile , may however also be relevant (Heise et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%